Polymeric nano-micelles: versatile platform for targeted delivery in cancer. (October 2014) - Mohamed, Salma; Parayath, Neha N; Taurin, Sebastien; Greish, Khaled
Polymeric micelles are among the most promising delivery systems in nanomedicine. The growing interest in polymeric micelles as drug delivery vehicle is promoted by the advantages they offer for hydrophobic anticancer agents. The size of most polymeric micelles lies within the range 10–100 nm ensuring that they can selectively leave the circulation at tumor site via the enhanced permeability and retention effect. Their unique structure allows them to solubilize hydrophobic drugs, prolongs their circulatory half-life and eventually leads to enhanced therapeutic efficacy. In addition, they can undergo several structural modifications to further augment tumor cell uptake. In this review, we will discuss various micellar systems that have been studied in preclinical and clinical settings.